Comparative Examinations of 99mTc-DMS Preparations Obtained by Labelling Dimercaptosuccinate Kits with Different Formulations. - Vanlić-Razumenić, Nada (Nuklearmedizin - NuclearMedicine, 1980)
The chemical and biological properties of two freeze-dried DMS kits for labelling with 99mTc (Tc P-5, manufactured by Boris Kidrič Institute, Vinča, and TCK-12, by CIS, Saclay) were compared. A method for the determination of the radiochemical composition of the injection solution is proposed: ascending Whatman 3 1 paper chromatography in 50% aqueous methanol. The chromatographic results correspond to the biologic activity of the preparations. The biodynamics of both radiopharmaceuticals were determined at intervals in rats. Maximum renal concentrations were achieved at 3-4 hrs post injection (52 % kidney and 3 % liver uptake for Tc P-5; 59 % kidney and 6 - 8 % liver uptake for TCK-12). The bench-lifes of the injection solutions were compared by determining organ distribution after standing of the solutions for 0,2 and 4 hrs. The Tc P-5 preparation was more stable, since the renal and hepatic concentrations were nearly constant. On the other hand, the hepatic concentration of TCK-12 was increasing during aging of the solution with a simultaneous decrease in renal concentration.